Inhibition of caspase-11 under inflammatory conditions suppresses chondrogenic differentiation - Veselá, Barbora; Bzdúšková, Jana; Ramešová, Alice; Švandová, Eva; Grässel, Susanne; Matalová, Eva (Tissue & cell, 2024)
Caspase-11 is the murine homologue of human caspases-4 and -5 and is involved in mediating the inflammatory response. However, its functions are often confused and misinterpreted with the more important and better described caspase-1. Therefore, this study focused exclusively on the specific roles of caspase-11, both in cartilage formation and in the inflammatory environment. The presence of caspase-11 during mouse limb development and in chondrogenic cell cultures was investigated by immunofluorescence detection. Subsequently, the function of caspase-11 was downregulated and the affected molecules investigated. The expression analysis applied for osteo/chondrogenesis associated factors and inflammatory cytokines. Simultaneously, morphological appearance of the micromass cultures was evaluated. The results revealed that caspase-11 is physiologically present during cartilage development, but its inhibition under physiological conditions has no significant effect on chondrogenic differentiation. However, in an inflammatory environment, inhibition and downregulation of caspase-11 leads to reduced differentiation of cartilage nodules. Additionally, reduced expression of several genes including Col2a1 and Sp7 and conversely increased expression of Mmp9 were observed. In the cytokine expression panel, a significant decrease was found in molecules that, along with the inflammatory function, may also be involved in cartilage differentiation. The findings bring new information about caspase-11 in chondrogenesis and show that its downregulation under inflammatory conditions reduces cartilage formation.
Keywords: buněčná diferenciace; myši; Cartilage; chrupavka; Cell Differentiation; iniciační kaspasy; Inflammation; zánět; chondrogeneze; Chondrogenesis; chondrocyty; kaspasy; Animals; Mice; zvířata; Cytokines; Caspases; cytokiny; Chondrocytes; Caspases, Initiator